Impact of Microfinance on Women Empowerment : A Study from the Decision - Making Perspective - Patel, Ritesh; Patel, Nikunj (Indian Journal of Finance, 2020)
Microfinance is considered as finance for the poor. The objective of the study was to evaluate the impact of microfinance on women empowerment from the decision-making perspective. The study was conducted on 512 SHG members belonging to the Aravalli and Mehsana districts of North Gujarat in 2019. The respondents from 12 villages of Bayad, Bhiloda, Kadi, and Mehsana talukas of North Gujarat participated in the study. The study was performed using paired sample t - test and empowerment index. The results of paired sample t - test revealed that after joining the SHGs, the decision-making ability of women was empowered significantly. Furthermore, it was observed that those women who participated in SHGs for longer duration and attended more meetings in a year were more empowered as compared to other women. The study has implications for SHG members. More women should be encouraged to join the SHGs as it empowers women on their decision-making ability. The members should conduct regular meetings by fixing a common time so that all the members can attend the meetings. The SHGs should focus on the sustainability of the women to continue as members.